Grave of the Globular Amphora culture from Koszyce in the chronological perspective - Włodarczak, Piotr; Szczepanek, Anita; Przybyła, Marcin M. (Baltic-Pontic Studies, 2021)
The grave of the Globular Amphora culture from site 2 in Koszyce, near Kraków, has already been the subject of a separate monograph and specialised analyses. This article addresses the chronology of the mass burial, resulting from a comparison of 23 radiocarbon dates obtained in three laboratories. The chronometric data were then juxtaposed with the results of isotopic analyses of strontium (87Sr/86Sr), carbon (δ13C) and nitrogen (δ15N). The analysis of the results indicates that the burial from Koszyce should most likely be dated to around 2880–2870 BC, which is slightly earlier than assumed in previous studies. It comes from a time when the Final Eneolithic barrow communities of the Corded Ware culture had already been present in the loess uplands of western Lesser Poland, and the burial ritual of some of the GAC groups was evolving towards the ritual of the Złota culture. The similar dating of these cultural phenomena makes it difficult to determine which community was responsible for the mass murder committed at Koszyce.